TECHNOLOGIES AND CONDITIONS OF THE HIGHER EDUCATIONAL INSTITUTION IMAGE FORMATION IN THE MASTER’S TRAINING PROCESS - Лохоня, Николай (SWorldJournal, 2021)
remain competitive: to know their business well, to be enterprising, to have a good reputation, as well as to take care of a positive image, a bright image in the minds of others. The image type is determined by consumer demands. Nowadays, a personal bran